Assessing the weathering of granitic stones on historical urban buildings by geochemical indices - Jorge Sanjurjo-Sánchez; Carlos Alves; Juan Ramón Vidal Romani (Earth Sciences Research Journal)
Weathering involves important processes that alter the original structure, texture and chemical components of rocks and minerals. Bulk changes produced by weathering in granitic rocks have been studied by several methods, including chemical weathering indices. They are based on the assumption that some ions are more easily leached from minerals in relation to others. Such methods have also been briefly tested on building stone but not in urban environments, where fast stone weathering rates are typically observed, mainly due to interaction of minerals with several pollutants and where other specific processes, such as salt weathering, can occur. The aim of this work is to discuss the use of weathering indices in the study of weathering rates on granitic stones applied in four historical buildings of an urban area. Results suggest that some factors can cause scatter of results in the relation indices vs. exposition age in the built environment, namely previous weathering degree in rock massifs and the quarry, different orientation of façades and different exposure to urban pollutants. Indices that consider some highly mobile cations that are present in other building materials (namely Ca that is related to leaching from mortar joints) should be avoided due to the uptake of such elements by the stone pores or used to assess this some types of weathering. Moreover, the use of some indices shows more reliable results.